Water and polymer dynamics in a model polysaccharide hydrogel: the role of hydrophobic/hydrophilic balance. Issue 2 (19th November 2014) - Rossi, B.; Venuti, V.; D'Amico, F.; Gessini, A.; Castiglione, F.; Mele, A.; Punta, C.; Melone, L.; Crupi, V.; Majolino, D.; Trotta, F.; Masciovecchio, C.
Abstract : The role of hydrophobicity/hydrophilicity balance in the gelation phenomena in water-swollen polymers is explored in a model polysaccharide hydrogel. Abstract : The molecular dynamics of water and a polymer matrix is here explored in a paradigmatic model of a polysaccharide hydrogel, by the combined use of UV Raman scattering and infrared measurements. The case example of cyclodextrin nanosponges (CDNS)/hydrogel is chosen since the simultaneous presence in the structure of the polymer matrix of both hydrophilic and hydrophobic sites mimics the complexity of polysaccharide hydrogels. In this way, the contributions provided by the balance between the hydrophilicity/hydrophobicity and the grade of entanglement of the polymer hydrogel to lead to the formation of the gel phase are separately accounted and evaluated. As main results, we found that the hydrophobic CH groups inserted on the aromatic ring of CDNS experience a more pronounced dynamic perturbation with respect to the carbonyl groups due to the collision between the solvent and vibrating atoms of the polymer. The overall results provide a detailed molecular picture of the swelling phenomena occurring when a chemically cross-linked polymer contacts with water or biological fluids and exploits the potentiality of UV Raman spectroscopy to retrieve dynamic information besides their structural counterpart obtained by the classical analysis of the basic features of vibrational spectra.